Nostalgia, Ethics, and Reparative Reading: Some Further Thoughts on Jean-Marc Vallée’s C.R.A.Z.Y. - Schwartzwald, Robert (Cinémas)

(untitled) (Cinémas, 2021)
This article is a further reflection by the author on Jean-Marc Vallée’s 2005 film C.R.A.Z.Y., in dialogue with questions and issues raised by reviewers of his 2015 book for the Queer Film Classics series. In particular, the article explores issues of nostalgia and ethics in the film: How does C.R.A.Z.Y. fit into the wave of nostalgic cinema in Quebec in the opening decades of the twenty-first century and especially its frequent mise en scène of father-son reconciliation? Looking at divergent views over the “work” performed by the film’s epilogue, how should the claim that Zac’s reconciliation with his father constitutes an ethical gesture be evaluated? Finally, in response to the mitigated responses of queer critics to the film and the sometimes normative framing of whether Vallée’s film is actually “queer,” the value of a reparative reading strategy is explored.